Passive muscle heating attenuates the decline in vascular function caused by limb disuse. (28th September 2021) - Hyldahl, Robert D.; Hafen, Paul S.; Nelson, W. Bradley; Ahmadi, Mohadeseh; Pfeifer, Brandon; Mehling, Jack; Gifford, Jayson R.
Abstract : Abstract: Limb disuse has profound negative consequences on both vascular and skeletal muscle health. The purpose of this investigation was to determine whether repeated application of passive heat, applied to the knee extensor muscles, could mitigate the detrimental effects of limb disuse on vascular function. This was a randomized, single‐blinded placebo controlled trial. Twenty‐one healthy volunteers (10 women, 11 men) underwent 10 days of unilateral lower limb immobilization and were randomized to receive either a daily 2 h sham (Imm) or heat treatment (Imm+H) using pulsed shortwave diathermy. Vascular function was assessed with Doppler ultrasound of the femoral artery and the passive leg movement technique. Biopsies of the vastus lateralis were also collected before and after the intervention. In Imm, femoral artery diameter (FAD) and PLM‐induced hyperaemia (HYP) were reduced by 7.3% and 34.3%, respectively. Changes in both FAD (4% decrease; P  = 0.0006) and HYP (7.8% increase; P  = 0.003) were significantly attenuated in Imm+H. Vastus lateralis capillary density was not altered in either group. Immobilization significantly decreased expression of vascular endothelial growth factor ( P  = 0.006) and Akt ( P  = 0.001), and increased expression of angiopoietin 2 ( P  = 0.0004) over time, with no differences found between groups. Immobilization also upregulated elements associated with remodelling of the extracellular matrix, including matrix metalloproteinase 2 ( P  = 0.0046) and fibronectin ( P  = 0.0163), with no differences found between groups. In conclusion, limb immobilization impairs vascular endothelial function, but daily muscle heating via diathermy is sufficient to counteract this adverse effect. These are the first data to indicate that passive muscle heating mitigates disuse‐induced vascular dysfunction. Key points: Limb disuse can be unavoidable for many of reasons (i.e. injury, bed rest, post‐surgery), and can have significant adverse consequences for muscular and vascular health. We tested the hypothesis that declines in vascular function that result from lower limb immobilization could be mitigated by application of passive heat therapy. This report shows that 10 days of limb immobilization significantly decreases resistance artery diameter and vascular function, and that application of passive heat to the knee extensor muscle group each day for 2 h per day is sufficient to attenuate these declines. Additionally, muscle biopsy analyses showed that 10 days of heat therapy does not alter capillary density of the muscle, but upregulates multiple factors indicative of a vascular remodelling response. Our data demonstrate the utility of passive heat as a therapeutic tool to mitigate losses in lower limb vascular function that occur from disuse. Abstract : Abstract figure legend A schematic of the primary study findings. Passive muscle heating attenuated the loss of vascular function that occurred due to 10 days of limb disuse.